Mobile and social media journalism : a practical guide - Adornato, Anthony (Washington D.C. : CQ Press, 2018)
A Practical Guide for Multimedia Journalism Mobile and Social Media Journalism is the go-to guide for understanding how today's journalists and news organizations use mobile and social media to gather news, distribute content, and create audience engagement. Checklists and practical activities in every chapter enable readers to immediately build the mobile and social media skills that today's journalists need and news organizations expect. In addition to providing the fundamentals of mobile and social media journalism, award-winning communications professional and author Anthony Adornato discusses how mobile devices and social media have changed the way our audiences consume news and what that means for journalists. The book addresses a changing media landscape by emphasizing the application of the core values of journalism-such as authentication, verification, and credibility-to emerging media tools and strategies. Learn about the latest industry trends, see examples from professional journalists, and watch video tutorials at MobileandSocialMediaJournalism.com.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Online journalism -- Study and teaching (Higher) -- United States; Journalism -- Study and teaching (Higher) -- United States; Social media -- United States; Mobile communication systems -- United States